Rapid recovery of homozygous Pr gene introgression lines in Indian tropical cauliflower backgrounds through combined use of morphological and molecular markers - Singh, Shrawan; Kumar, Sandeep; Verma, Vinay (Frontiers in Plant Science, 2025)
Anthocyanin is a groups of secondary metabolites which are strong antioxidants. Biofortificaiton of commonly used foods for anthocyanin enhance the chances of its intake and enjoy health benefits by common people. The study aimed at rapid anthocyanin biofortification of tropical cauliflower by combining morphological and marker-assisted selections. Two tropical varieties, Pusa Ashwini (PA) and Pusa Kartiki (PK), were crossed with the donor KTPCF-1 (or PPCF-1) of the snowball group. The F2, BC1F1, and F2:3 populations from PA/PPCF-1 and PK/PPCF-1 supported a single dominant gene (Pr) for purple colour in both the seedling apical and curd portions. The F2 and BC1F2 plants were first selected for purple curd and morphological traits specific to tropical cauliflower, namely, semi-erect leaf habit, October–November maturity, and tropical flowering habit. A total of 40 and 30 purple curding plants were selected in F2 and BC1F2, respectively. Visual detection of homozygous and heterozygous purple plants was unreliable. Thus, these 70 plants were screened using two codominant (BoMYB2m and BoMYB4m) and one dominant (BoMYB3m) markers for forward selection. A total of 19 plants in F2 and 21 plants in BC1F2 were found homozygous for the Pr gene, of which 13 F2 plants and all 21 BC1F2 plants produced sufficient seeds to advance F2:3 and BC1F2:3, respectively. The progenies showed a significant increase in total anthocyanin content. The marker-assisted selection (MAS)-derived PrPr progenies, namely, PC2304-21, PC2304-93, PC2304-64, PC6704-16, and PC6704-36, were the most promising with higher curd yield (>17.2 t/ha), hence advanced to F3:4. These tropical-type progenies are of immediate breeding use for anthocyanin-rich varieties/hybrids to harness the associated benefits in the tropics.